The economic value of domestic science - Finley, Lena M. (My University, 1905)
Introduction: The purpose of this thesis is to show the relation of economics to domestic science and to emphasize the importance of the latter science as a factor which enters into the efficiency of the individual laborer. Domestic economy is quite commonly conceded to be one of the most important sciences of today; but popular opinion limits its application to the home when in reality its scope is wider than that of any other science. Its relation to certain phenomena of economics is especially close; and to none closer than to the labor-power of any community. It is this intimate connection of individual and communal efficiency of labor with domestic science that will form the basis of the following discussions. The history of the past ages of man proves that the civilization of the early ages was of very low degree. The domestic science part of their lives, we find, "was indeed very poor and crude. They lived upon roots, grasses, and various kinds of wild nuts, for the vegetable part of their diet, and the animal diet consisted of the wild animals that they could capture. As a rule all their food was eaten in the raw state. According to their ideas fresh meat was not at all necessary for they would often eat meat partially or even wholly spoiled and think that they had a treat. Not very long ago the Australians considered themselves haply if they could but secure whale's flesh that was beginning to putrefy. Other animals eaten by the early races were: beavers, rats, toads, bears, foxes and rhinoceri. In fact as near as can be determined, these ancestors of ours would eat anything which they could capture by any means and would eat it in anyform.
Citation: Finley, Lena M. The economic value of domestic science. Senior thesis, Kansas State Agricultural College, 1905.
Morse Department of Special Collections
Keywords: Cooking; Sanitary Homes; Domestic Science; Theses